2021
DOI: 10.26633/rpsp.2021.33
|View full text |Cite
|
Sign up to set email alerts
|

El panorama de los ensayos clínicos sobre COVID-19 en América Latina y el Caribe: evaluación y desafíos

Abstract: Se está llevando a cabo un número considerable de ensayos clínicos en todo el mundo en respuesta a la pandemia de COVID-19, incluso en países de ingresos bajos y medios como los de América Latina y el Caribe. Sin embargo, la abundancia de estudios no necesariamente acorta el camino para encontrar intervenciones seguras y eficaces frente a la COVID-19. Se analizaron los ensayos para el tratamiento y la prevención de la COVID-19 de los países de América Latina y el Caribe que están registrados en la Plataforma d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 7 publications
0
8
0
2
Order By: Relevance
“…Remarkably, 198 studies for candidate therapeutics and only 11 studies exploring candidate vaccines were found, signaling a relatively low participation of LAC population in this type of research. This is more worrying due to the fact that RCTs protocols for such studies have also been found to be of low quality and potential waste of research resources (14). This finding might have implications for understanding the actual effects of different health technologies on the region's population, as most of the COVID-19 scientific knowledge would need to be imported from elsewhere.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Remarkably, 198 studies for candidate therapeutics and only 11 studies exploring candidate vaccines were found, signaling a relatively low participation of LAC population in this type of research. This is more worrying due to the fact that RCTs protocols for such studies have also been found to be of low quality and potential waste of research resources (14). This finding might have implications for understanding the actual effects of different health technologies on the region's population, as most of the COVID-19 scientific knowledge would need to be imported from elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…To identify grey literature, registry of trials, and pre-print articles, the electronic database search was also supplemented by searching the Living Overview of the Evidence (L-OVE) COVID-19 Repository by the Epistemonikos Foundation, and searching the references of evidence syntheses that were found when assessing the eligibility of the articles. Additionally, registries for studies that are planned to be conducted were complemented with the clinical trials found by Carracedo S et al 2021 (14). The search strategies that were used in each database are described in the S1 Supporting information 1.…”
Section: Search Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify grey literature, registry of trials, and pre-print articles, the electronic database search was also supplemented by searching the Living Overview of the Evidence (L-OVE) COVID-19 Repository by the Epistemonikos Foundation, and searching the references of evidence syntheses that were found when assessing the eligibility of the articles. Additionally, registries for studies that are planned to be conducted were complemented with the clinical trials found by Carracedo S et al 2021 [ 15 ]. The search strategies were built based on all potential synonyms of “COVID-19”, combining with geographical terms that could point out towards the LAC region, or any of the countries that are part of the region.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, research funding has also been questioned in terms of the distribution and sources for achieving a fair and sustainable research and development environment [ 14 ]. In LAC, a study searching for COVID-19 trials on treatment and prevention in the region identified “a trend towards small repetitive non-rigorous studies that duplicate efforts and drain limited resources without producing meaningful conclusions on the safety and efficacy of the interventions being tested” [ 15 ]. However, apart from this study it is unknown what are the trends of empirical research in LAC during the COVID-19 pandemic, in a context where institutional development for health research has progressed in the region but has been reported as generally uncoordinated and disaggregated, and uneven between countries [ 16 ].…”
Section: Introductionmentioning
confidence: 99%